2011
DOI: 10.1016/j.immuni.2010.12.016
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocytes Negatively Regulate Lymph Node Lymphatic Vessel Formation

Abstract: Lymph node lymphatic vessels (LNLVs) serve as a conduit to drain antigens from peripheral tissues to within the lymph nodes. LNLV density is known to be positively regulated by vascular endothelial growth factors secreted by B cells, macrophages, and dendritic cells (DCs). Here, we show that LNLV formation was negatively regulated by T cells. In both steady and inflammatory states, the density of LNLVs was increased in the absence of T cells but decreased when T cells were restored. Interferon-γ secretion by T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
217
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(236 citation statements)
references
References 43 publications
16
217
0
3
Order By: Relevance
“…50,51 Finally, T cell-derived cytokines including IFN-γ, IL-4 and IL-13 have been shown to directly inhibit lymphangiogenesis. 46,52 Consistent with previous studies in obese mice and patients, 26 we noted a marked increase in VEGF-C expression in tissues and serum harvested from obese HFD-fed C57BL/6J mice. This effect has a key role on glucose homeostasis in obesity by regulating macrophage infiltration and differentiation.…”
Section: Discussionsupporting
confidence: 90%
“…50,51 Finally, T cell-derived cytokines including IFN-γ, IL-4 and IL-13 have been shown to directly inhibit lymphangiogenesis. 46,52 Consistent with previous studies in obese mice and patients, 26 we noted a marked increase in VEGF-C expression in tissues and serum harvested from obese HFD-fed C57BL/6J mice. This effect has a key role on glucose homeostasis in obesity by regulating macrophage infiltration and differentiation.…”
Section: Discussionsupporting
confidence: 90%
“…Toll-like receptor (TLR)-4 is highly expressed in LECs and contributes to lipopolysaccharide (LPS)-induced lymphangiogenesis by chemotactic recruitment of macrophages ). Notably, a recent study showed that lymph nodes in athymic nude mice have excessive lymphatic vessels and that interferon-g released by T lymphocytes negatively regulates lymph-node lymphatic vessel formation by suppressing key lymphatic molecules (Kataru et al 2011). Importantly, lymphatic vessels can perform functions beyond passive conduits for immune response.…”
mentioning
confidence: 99%
“…28 On the other hand, the loss of Prox-1 activity results in defective lymphangiogenesis. 13,14 In a murine contact hypersensitivity model, downregulation of Prox-1 is inversely correlated with local TNF and interferon-γ production. 29 Furthermore, mice heterozygous for a mutation that inactivates Prox-1 exhibit features of leaky lymphatic vessels and are prone to develop obesity and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of the transcriptional activity of Prox-1 has previously been associated with suppression of LEC tube formation 13 and lymphatic sprouting of TD rings, 14 underscoring its fundamental role for determining the lymphatic phenotype. This was confirmed as shown in Figure 4A, which shows that Prox-1 mRNA levels are decreased 2.3-fold when LECs are incubated with TNF (P<0.05 compared with control).…”
Section: Apoa-i Maintains Prox-1 Expression In Lecs In the Presence Omentioning
confidence: 94%